Integrative effects of saffron and physical activity on endurance performance, quality of life, cognitive, emotional, and metabolic outcomes in age-related and neurodegenerative diseases - Li, Lingyun; Wang, Kehai (Frontiers in Nutrition, 2025)
Age-related diseases, including cardiovascular disorders, type 2 diabetes, neurodegenerative conditions such as Alzheimer's and Parkinson's disease, and age-related eye diseases, represent leading causes of disability and mortality worldwide. Growing evidence highlights the therapeutic promise of non-pharmacological interventions, notably saffron (Crocus sativus L.) and structured exercise, both of which exert pleiotropic effects through antioxidant, anti-inflammatory, and neuroprotective pathways. In this review, we summarize current experimental and clinical data on saffron's bioactive compounds, crocin, crocetin, and safranal, and their capacity to modulate lipid metabolism, insulin sensitivity, mitochondrial function, and protein aggregation. Parallel findings from exercise research demonstrate improvements in cardiovascular function, glycemic control, neuroplasticity, and ocular health. Importantly, emerging studies reveal synergistic benefits when saffron supplementation is combined with physical activity, resulting in amplified improvements in vascular remodeling, glycemic regulation, neurotrophic signaling, and behavioral outcomes. These complementary interventions target shared molecular pathways, including PI3K/Akt/mTOR signaling, SIRT1–PGC-1α activation, Nrf2-mediated antioxidant defense, and modulation of inflammatory cytokines. Taken together, saffron and exercise represent safe, accessible, and multi-target strategies that may delay or attenuate the progression of aging-related diseases. Future large-scale, long-term clinical trials are warranted to establish optimal protocols and to integrate these interventions into preventive and therapeutic frameworks for healthy aging.